Optimalisasi Peran Masjid Dan Edukasi Bencana Untuk Ketahanan Sosial Kelurahan Betungan - Yasa, Pri Yogha; Wandi, Dehar; Adiansyah, Febri; Juniansyah, Dedy; Hartono, Andi; Fredricka, Jhoanne; Khairil, Khairil; Zulita, Leni Natalia (Jurnal Dehasen Untuk Negeri, 2025)
Al-Anshar Mosque in RT 04/RW 01 Betungan Sub-district functions not only as a place of worship for residents but also as a stopover for intercity travelers, prompting the need for improved comfort, cleanliness, and order. Although residents are aware of earthquake risks, accessible educational visual media is still needed to strengthen preparedness. This activity aimed to optimize the mosque's role as a socio-educational space and enhance disaster awareness through a participatory, community-based approach. The program included community clean-up, installation of facility signboards, distribution of hygiene posters, and visual-based earthquake education. The results indicated increased community awareness of environmental cleanliness and disaster preparedness, with the mosque also serving as an effective educational space for visitors. The initiative contributes to social resilience and is potentially replicable in other disaster-prone areas.